Maritime strategies in Asia - Schwarz, Jürgen; Herrmann, Wilfried A; Seller, Hanns-Frank (White Lotus, 2002)
The first-ever major study on maritime strategies in the Asian region and the technical co-operation possibilities with German maritime industries, provides an up-to date and comprehensive assessment of the maritime strategic concepts and the navy capabilities of the coastal countries of the Asia-Pacific region. From a European perspective Asia, stretching from the Indian Ocean to the Far Eastern regions, is of crucial importance for world trade and international stability. But global and regional prosperity and stability are closely related to the indispensable precondition of freedom of navigation for commercial shipping and the unrestricted use of sea-lanes of communication (SLOCs). For many years, the prime maritime concern was militaly, not economic, as the United States and other nations required secure maritime transport through the sea-lanes of the Asian regions in times of military tensions and war. Now the emphasis has shifted to the economic component, but freedom of navigation for commercial shipping will still have to be guaranteed by military or maritime means, and depends to a growing part on modem technical equipment. What are the major concerns? How well are nations in the region and outside it prepared to deal with these challenges? Are their navies equipped to match the new security environment and to defend the national interests? What are the possibilities of international co-operation? An international team of experts deals with these questions in this joint study led by the "Asia Strategic Institute Hong Kong" and the "Institute of International Relations" at the German Federal Armed Forces University in Munich.